PERTUMBUHAN DAN HASIL TANAMAN MELON PADA BERBAGAI MEDIA TANAM DAN SISTEM PEMBERIAN HARA - Ikrimah, Dhiya Ul; Pratama, Deni; Zasari, Maera (JURNAL AGROTROPIKA, 2025)
One of the efforts to deal with this problem can be through the use of planting media and the right nutrient system. This study aims to determine the influence of the type of bark planting medium, nutrient system and interaction on the growth and yield of Honey Dew. This study uses a Factorial Group Random Design. Treatment cempedak bark planting medium with drip irrigation, cempedak bark planting medium with direct watering, sengon bark planting medium with drip irrigation, sengon bark planting medium with direct watering, pine bark planting medium with drip irrigation, and pine bark planting medium with direct watering. Research of results showed that the use of bark planting media had a significant effect on fruit length and fruit diameter. The nutrient system has a significant effect on plant height, number of leaves, stem diameter, fruit weight, fruit length, number of seeds in the fruit, moisture content and sugar content. The interaction of the type of bark planting medium with the nutrient system only had significant effect on the percentage of potential fruit falls. Cempedak bark planting media shows the best growth and yield of Honey dew. The drip irrigation nutrient application system showed the best honey dew growth and yield and the interaction of pine bark planting media type and drip irrigation system gave the best honey dew crop yield.Keywords : honey dew, sengon bark, cempedak bark, pine bark, nutrient application system.